Non-invasive evaluation of cerebral hemodynamic and intracranial pressure in pediatric neuroinfections - GeorgiyntsМ. А.; КоrsunovV. А.; ОlkhovskaО. М.; StoliarovК. E. (Regulatory Mechanisms in Biosystems, 2018)
The study of intracranial pressure (eICP), cerebral perfusion pressure (eCPP), cerebral blood flow index (CFI), zero flow pressure (ZFP) in 49 children hospitalized in the intensive care unit with severe course of neuroinfections was carried out. The level of consciousness was determined by the Glasgow pediatric scale. Monitoring of central and peripheral hemodynamics (ECG, heart rate, systolic, diastolic and mean blood pressure, and cardiac output), pulse oximetry, capnography, hemoglobin, hematocrit, total protein, urea, creatinine, lactate, glucose and serum electrolytes was done. An ultrasound scanner was used to perform ultrasound duplex scanning of blood flow in the left and middle cerebral artery (MCA), measuring maximum, minimum and average blood flow velocities, pulsation index (PI), and resistance index (RI). Based on the formulae of Edouard et al. indicators of eCPP, ZFP, CFI, eICP were calculated. The eSCP was also determined by the formulae of Kligenchöfer et al. and Bellner et al. All patients were divided into group I with RI > 1.3 and group II with RI < 1.3. It was found that eCPP in the group I was significantly less (29.5 ± 1.3 mm Hg) than in the II group (41.6 ± 1.7 mm Hg). Despite the lack of a reliable difference in blood pressure between groups I and II, the difference in eCPP was found due to a significant difference in eICP 34.6 ± 1.4 and 27.6 ± 0.89 mm Hg in I and II groups respectively. ZFP in group I was significantly higher than in group II. The indexes of the Glasgow coma scale was significantly lower in group I and 7.8 ± 0.6 points. There were observed direct moderate correlations between systolic blood pressure, cardiac output and eSRP and CFI, presumably associated with a loss of autoregulation. CFI in the group I was lower than in the group II. Thus, non-invasive examination of cerebral flow in MCA by duplex sonography revealed that PI > 1.3 is an informative marker of intracranial hypertension and reduction of cerebral perfusion, which is common in children with neuroinfections. To determine the eSRP and CFI it is advisable to use the formula of Edouard et al. and to determine the eICP the formula of Kligenchöfer et al. The obtained data can be useful for objectifying the severity of the condition, predicting the outcomes of neuroinfections, choosing the directions of intensive care and evaluating its effectiveness.